Referral patterns and outcomes of children who failed Modified Checklist for Autism in Toddlers screening during routine health screening at maternal and child health clinics in the northeast district of Penang: A retrospective cohort study - Ranjini Ambigapathy; Sathyabama Ramachandram; Fairuz Fadzilah Rahim (Malaysian Family Physician, 2024)
Introduction: Autism spectrum disorder (ASD) is a developmental disability that causes significant social, communication and behavioural challenges. The Modified Checklist for Autism in Toddlers (M-CHAT) is a parent-administered screening questionnaire for ASD used at 18 and 36 months of age. This study aimed to determine the outcomes of children who failed M-CHAT screening during routine health screening at maternal and child health clinics in northeast district, Penang and the prevalence of ASD among those with a final diagnosis. Methods: This retrospective cohort study was conducted at 12 maternal and child health clinics. All children who failed M-CHAT screening at 18 and 36 months from January 2017 to December 2021 and received a final diagnosis before 31 March 2022 were recruited. All information required was recorded in a data collection form and analysed using SPSS. Multiple logistic regression was performed to assess the association between the factors and ASD status. Results: Eighty-two children failed M-CHAT screening. Fifty children did not receive a final diagnosis. Among 32 children who received a final diagnosis, 25 were diagnosed with ASD (78.1%). Among the children who underwent M-CHAT screening, the odds of having ASD increased by a factor of 1.2 for every 1-unit increase in age at final diagnosis. Conclusion: In northeast district, Penang, more than half of children who fail M-CHAT screening have no final diagnosis. The specificity of the M-CHAT is 78.1% among children with a final diagnosis of ASD. The age at final diagnosis is positively associated with the diagnosis of ASD.